COMPARATIVE STUDY BETWEEN CREATIVITY MEASURES: TCTT VERSUS CREA - López Martínez, Olivia; Navarro Lozano, Juan (Anales de Psicología / Annals of Psychology, 2008)
The general mission of this work is to make a comparative study between two tests of valuation of the creativity. The used total sample is of 96 students, pertaining to a School of Infantile and Primary Education, of the region of the Plateau (municipality of Jumilla) in the Region of Murcia (Spain). The center was chosen at random, in the region, of between those of double line allowing possible most equivalent control groups. We have wanted to resist the results obtained in the Test of Creative Thought of Torrance (TTCT), test with long-haul, and in the test of Creative Intelligence CREA of Corbalán and collaborator, fruit of the last investigations to evaluate the creativity.